INFLUENCE OF WORK ENVIRONMENT, SELF-CONCEPT AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE SATISFACTION - Nugroho, Agung Dwi; Wahjoedi, Tri (Jurnal Manajemen, 2022)
This study aims to examine the effect of Work Environment, Self-Concept, and Organizational Commitment on Employee Job Satisfaction. The population in this study were employees of PT MATU Pasuruan, East Java, Indonesia, with a saturated sampling of 52 employees. Data analysis used SPSS 23 program, with instrument testing namely validity and reliability, classical assumption test, and hypothesis testing. The results of this study indicate that the work environment, self-concept and organizational commitment have a significant effect both individually and simultaneously on employee job satisfaction. Organizational commitment is the variable with the most dominant influence. From the findings, organizations and managers are expected to focus on developing a work environment for their workers in various ways, e.g.: equipping tools, creating comfort and stability. This includes recognizing workers' contributions, communicating company progress and achievements to workers, empowering workers, providing work-life balance, and the knowledge and skills required for optimal achievement. Improving all of these factors can increase the worker's self- concept and commitment in the organization which leads to job satisfaction. This research enriches information/theory regarding the relationship between work environment, self-concept and organizational commitment on employee job satisfaction